Genome Editing and Defense against Its Misuse - J. Lakota (Вестник войск РХБ защиты)
Human genome editing methods (“genetic scissors“) may be possibly used for biological attacks of various biological targets, including humans.We should set up an international surveillance scheme to control the use of this method and to detect cases of hidden use of these destructive agents created on its basis.Relevance. Human genome editing has been implemented into clinical practice since 2021 to cure different, mainly hereditary diseases. This method is quite promising and in the long run it can be used to cure contagious and somatic diseases as well.The purpose of the study is to evaluate possible risks of misuse for this method.The source base of the study. Scientific publications and research papers, available in PubMed.Research method. Analytical.Results. It has been shown that genome editing systems can block, remove or restore its own genes or human genome fragments. They can be employed to destroy whole ecosystems, to develop brand-new massive biological weapons to kill the population of certain countries. They are even able to change an evolutionary path of our species, and this may lead to its total extinction within several generations. Defense Advanced Research Projects Agency, DARPA has a particular focus on the development of tools that can identify the human genome editing, block possible changes and eliminate the consequences.Conclusions. The fact that DARPA is so interested in tools mentioned above proves that genome editing is anymore not an experimental tool. Experts who realize the state of things in terms of biological warfare nowadays are concerned with the possible misuse of this tool. The use of genome editing should be regulated by a special Protocol to Convention on the Prohibition of the Development, Production and Stockpiling of Bacteriological (Biological) and Toxin Weapons and on their Destruction. Because this protocol doesn’t exist yet, the national regulatory authorities are obliged to establish limits for use of products that are based on these methods. They also should be able to prevent its misuse.